PERLINDUNGAN KONSUMEN PADA PRODUK KREDIT PEMILIKAN RUMAH DITINJAU DARI PERSPEKTIF ISLAM (Studi Di Bank Tabungan Negara Kantor Cabang Syariah Bogor) - Siti Indah Dahlia; Rully Trihantana; Ria Kusumaningrum (SAHID BANKING JOURNAL, 2022)
This research is motivated by the importance of consumer protection for banking customers, especially housing. The purpose of this research is to find out the contract and mechanism of mortgage financing, the responsibility of bank BTN as a provider of mortgage products, and whether there are Islamic values in consumer protection at Bank BTN Syariah KC Bogor. This research was conducted at Bank BTN Syariah KCS Jalan Jendral Sudirman Bogor. This research is qualitative and the data collection method is by conducting interviews, observation and documentation at BTN KCS Bogor. The analysis used in this research is descriptive qualitative. The results of the study show that the contracts used in mortgage financing at Bank BTN KCS Bogor are murabahah and wakalah. Consumer protection still needs to be improved.